Perceived discrimination, level of coping, adaptation and psychological well-being of the immigrant. Salinas, Ecuador. - Díaz-Amador, Yanedsy; Manuel-Reyes, Víctor; Soto-Rodríguez, Maykel (Enfermería Global)
Introduction: The study of the psychological well-being of the immigrant population has recognized perceived discrimination and the level of coping as an important onset of stress in the host country, this in turn calls into question the impact that may exist on positive psychological functioning. of this population. Objective: Determine the relationship between perceived discrimination, level of coping and adaptation and the psychological well-being of the immigrant. Material and method: Quantitative, descriptive, correlational-predictive, non-experimental study. 149 immigrants residing in the Salinas canton, Ecuador, participated from January to June 2024. The immigrants were socio-demographically characterized and the level of perceived discrimination, level of coping, and psychological well-being were measured. The correlation between the variables was calculated using bivariate analysis (Spearman's Rho coefficient, 95% CI) and multivariate analysis (RLO), analyzed with SPSS version 27 software. Results: Mean age of immigrants 34.4±36.7 years, 72.48% women, 61.75 % university education, predominantly of Cuban origin 50.34%, 81.21% with permanent residence, 74.50% rented. A positive correlation (r=0.122, p=<0.05) between age, sex, migratory status, perceived discrimination and level of coping with some dimensions of psychological well-being, which predicts that these factors are predictors of the psychological well-being of immigrants. Conclusions: Foreigners, mainly Latino, go through a complex set of situations where immigration status, perceived discrimination, and the level of coping and adaptation turned out to be predictive factors in the psychological well-being of immigrants.